Autofluorescence bronchoscopy - Debeljak, Andrej (Endoskopska revija, 2008)
Autofluorescence is a form of emission of light of longer wave length occurring after a light of a specific wavelength has been applied to bronchialmucosa. The response of malignant and premalignant tissues differs from that of healthy bronchial mucosa. Dysplasia and carcinoma in situ, which are only a few unit cells thick and a few milimeters in diameter, have different fluorophore concentrations and show pathological vascularisation. Early malignant changes, dysplasia and carcinoma in situ are difficult to detect with conventional white light bronchoscopy even by experienced bronchoscopists. Autofluorescence bronchoscopy (AFB) is a very sensitive tool for detecting preneoplastic changes and carcinoma in situ, and yields up to three times more accurate results than light bronchoscopy. The method is performed under topical anaesthesia and prolongs the procedure time by five toten minutes. The complication rate is similar to that reported for white light bronchoscopy. New techniques have been clinically evaluated with the aimto improve sensitivity and specificity of the method, to simplify the procedure and to objectify the results. AFB facilitates the diagnosis of premalignant changes of bronchial mucosa and early bronchial carcinoma in high-risk patients, and enables clinicians to study carcinogenesis. The methodwill offer the possibility for treating patients by the endoscopic approach, and promises to improve prognosis in patients with lung cancer. AFB is not used in everyday diagnosis of primary and secondary invasive bronchial carcinoma. Its future use should be restricted to the detection of preneoplastic changes and carcinoma in situ in groups at high risk for the development of lung cancer.
Keywords: diagnostika; dihala; bronhiji; bronhoskopija; endoskopsko zdravljenje